A regulação do investimento estrangeiro direto e suas implicações para o caso brasileiro - Guimarães, Bernardo Costa Peterli (2018)
In the last decades Brazil adopted a successful policy of attracting foreign investment which can be attested by the fact that in 2017 we become the 4th largest recipient of foreign direct investment in the world. Our need to increase investments rate as well as to finance our current account deficits are the main reasons that made this policy so active. Nevertheless, the absence of control over the inflow of foreign investments does not allow the country to assess the impacts they have on its development and adherence to national interests such as autonomy, national defense, technology or account balance sustainability. Thus Brazil is going against the world trend that has been the creation or strengthening of instruments that regulate the entry of foreign investment precisely in order to ensure that they comply with these objectives. The great motivator for the strengthening of these controls has been the participation of China in the international scene with the implementation of the "China 2025" program, which seeks to make it a relevant player in sectors such as aerospace, robotics, integrated circuits or energies including by the acquisition of international companies holding such technologies. The present work therefore seeks to discuss and analyze whether Brazil has a regulatory framework for the entry of foreign investment adequate for the development of the country which also takes into account its national interests. In order to do so, we present how foreign direct investment can impact our economy, how China has appeared on the international scene and how this has been reflected in the regulation of foreign investment, especially in countries such as USA, European Union, China, Australia and Canada, and finally, how Brazil has prepared itself and what mechanisms it might use to improve the use of these resources for its development.